Angiotensin System Inhibitors May Improve Outcomes of Patients With Castration-Resistant Prostate Cancer During Abiraterone Acetate Treatment—A Cardio-Oncology Study - Wilk, Michał; Waśko-Grabowska, Anna; Skoneczna, Iwona; Szmit, Sebastian (Frontiers in Oncology, 2021)
Background: Abiraterone acetate (ABI) therapy improves overall survival in metastatic prostate cancer (PC) patients, however this effect may be diminished by concurrent comorbidities. We aimed to evaluate the influence of pre-existing chronic diseases and concomitant medications on the course of ABI treatment among post-chemotherapy patients with metastatic castration resistant prostate cancer patients (mCRPC). Methods: From the Polish National Health Fund database, we identified 93 post-chemotherapy, mCRPC patients, who were qualified for ABI treatment in our oncology center between 2014-2018. Survival curves and Cox proportional hazard models (univariate and multivariate) were used to determine the predictors for longer time to treatment failure (TTF) of ABI therapy. Results: Median TTF was 9,8 months (IQR: 0,6 – 56,5) Factors associated with longer TTF were: well controlled hypertension (HR 0,59; 95%CI: 0,38-0,90; p=0.02), stable coronary artery disease (HR 0,56; 95%CI: 0,33-0,95; p=0.03), the use of angiotensin system inhibitor (ASi) (HR 0,61; 95%CI 0,4-0,94; p=0,02). Patients who were receiving ASi had median TTF of 12,2 months versus 5,8 months in men who did not receive ASi before ABI initiaion. At the start of ABI therapy, the aforementioned groups did not differ in terms of well known prognostic factors: Gleason score, PSA level, or the number of patients with visceral metastases. In a multivariate analysis, the use of ASi remained statistically significant, even after adjustment for well-known oncological factors. (HR 0.57; 95% CI, 0.34- 0.98; p=0.04). Conclusions: The use of ASi may enhance and prolong ABI therapy in post-docetaxel mCRPC patients, and may potentially be considered a new, non-oncological, predictive factor for longer TTF. This association requires a prospective validation.